Boosting work engagement through leader tolerance: the chain mediation role of perceived organizational support and organizational identification - Zhang, Yuan; Zhang, Jingqun; Hao, Kui (Frontiers in Psychology, 2025)
IntroductionTo enhance competitiveness, numerous organizations have introduced control and penalty systems to manage employee work errors. However, these systems have often backfired, negatively impacting employees’ emotions and behaviors. Recognizing the critical role of leadership in error management, this study examines how leaders’ tolerance of their followers’ mistakes influences employees’ work engagement, drawing on Affective Events Theory (AET).MethodsAnalyzing data from 435 front-line public health service staff, this study investigates the relationship between leader tolerance and employees’ work engagement. First, the Harman one-factor test was employed to assess common method variance (CMV) in the research data. Second, the reliability and validity of the data were evaluated using the Cronbach’s α, KMO, AVE, CR, and CFA. Finally, the proposed mediating hypotheses were tested using Model 6 in the SPSS Process macro (version 4.1).ResultsWe found that leader tolerance significantly boosts employees’ work engagement. Furthermore, our results confirm the mediating roles of perceived organizational support (POS) and organizational identification in the relationship between leader tolerance and work engagement. This study also validates the hypothesized chain mediation model, demonstrating how POS and organizational identification together mediate the influence of leader tolerance on employees’ work engagement.DiscussionThese results underscore the importance of leadership styles that accommodate employees’ errors and emphasize the crucial roles of organizational support and identification. The findings highlight the need for organizations to adopt more supportive leadership approaches rather than relying solely on control and penalty systems. The study concludes by stating the theoretical and practical implications, along with recommendations for future research on leader tolerance.